STUDENTS’ PERCEPTIONS ON THE ACCENTS OF NON-NATIVE ENGLISH SPEAKERS IN INTERACTIVE LISTENING AND EXTENSIVE SPEAKING CLASS - Saipullah, Habib Muhar; Syahri, Indawan; Susanti, Rini (English Community Journal, 2021)
The objectives of this study were (I) to know the students' perceptions on the accents of non-native English speakers in the videos and (II) to identify the challenges in listening to the accents of non-native English speakers in Interactive Listening and Extensive Speaking class. The writer used descriptive qualitative in this study. The participant of this study was all students in the third semester of Interactive Listening and Extensive Speaking classes from English Education Study Program. The data were collected by giving the questionnaire to the participants, then analyzing them by using the formula of percentage calculation to be interpreted descriptively. The main finding showed that most of the students in  Interactive Listening and Extensive Speaking classes had a positive perception of the accent of non-native English speakers. They believed that understanding different accents could enrich their knowledge of English accents and improve their listening skills. The challenges and difficulties that students identified in listening to the accents of non-native English speakers did not create a negative perception. They believed that listening to the non-native English accents is not easy because it was challenging for the difficulties in understanding them.